The Khorsabad/Dūr-Šarrukin Excavation and Its Impact on the Asar-ı Atika Nizamname’s - Bülent Genç (Anadolu Araştırmaları)
When Paolo Emilio Botta was appointed to Mosul as the French consul in the last quarter of the 19th century, significant developments in Mesopotamian archeology occurred. During Botta's studies in the Mosul area, a resident of the village of Khorsabad mentioned reliefs and inscriptions on top of a hill. Botta dispatched a group of workmen to Khorsabad on March 20, 1843, after three months of arduous work in Kuyunjik. However, problems began to arise shortly after his work in Mosul. Particularly Mehmed Pasha in the province creates various obstacles. In this context, we searched the Ottoman Archives to learn more about Botta's excavation permits and documents, the obstacles created by the Pasha ofMosul, and the details, background, and correspondence of Botta's story in Khorsabad. We came across many documents, which included details as to the problems Botta experienced in Khorsabad, the conditions about the excavation permit and the construction of the excavation house, the plan of the excavation house mentioned by Botta, which was shown to be like a castle next to the village houses and sent to Istanbul, and the petitions of the villagers against Botta's research and the excavation house. In this article, we tried to understand how this period was understood and handled by re-reading Botta's excavation periods, permit documents, and the problems he encountered through the available documents. In particular, in the context of Khorsabad, we reviewed the excavation permission and articles given to Botta and examined its contribution to the Asar-ı Atika Regulations.